Preparation method of iron hafnate

Through liquid phase mixing and evaporation and drying method and multiple mud embryo treatments, the problem of uneven texture of iron hafnate is solved, and the texture uniformity and high-temperature performance of iron hafnate is improved. It is suitable for ceramic additives for hot-end components of aircraft engines.

CN119551731APending Publication Date: 2025-03-04XIAN JI-LI ELECTRONIC & CHEM ENG CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411599044.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-11
Publication Date
2025-03-04

AI Technical Summary

Technical Problem

The existing preparation methods for iron hafnate lead to uneven texture and cannot meet the technical indicators and requirements of high-temperature ceramic additives for hot end components of aircraft engines.

Method used

Iron fluoride hafnate was prepared by liquid phase mixed evaporation and drying, followed by multiple mud embryo treatments and defluorohydrolysis reactions, and finally high-temperature shaping treatment was carried out to ensure the uniform texture of iron hafnate.

Benefits of technology

The uniformity of the texture of iron hafnate is achieved, and the technical indicators and requirements of aircraft engine hot end components for high-temperature resistant ceramic additives are met, and it is easy to operate and industrially produced.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

In order to solve the technical problems that iron hafnate prepared by the existing iron hafnate preparation method is uneven in ground and cannot meet the technical index requirements of aero-engine hot end components and the like on high-temperature ceramic additives, the invention provides a preparation method of iron hafnate. The preparation method comprises the following steps: firstly, dissolving hafnium oxide in hydrofluoric acid, then adding iron trioxide into the hydrofluoric acid, carrying out evaporation drying treatment to obtain an iron hafnium fluoride block material, and crushing and sieving the iron hafnium fluoride block material to obtain iron hafnium fluoride powder; then preparing the iron hafnate fluoride powder into a mud blank, heating and raising the temperature to carry out defluorination hydrolysis reaction, and repeating the process until fluorine ions meet requirements to obtain an iron hafnate amorphous substance; and finally, carrying out high-temperature qualitative treatment on the amorphous iron hafnate substance to obtain a porcelain-like iron hafnate finished product. According to the method, the texture uniformity of the iron hafnate can be ensured through liquid-phase mixing and drying by distillation, multiple times of mixing treatment with mud and defluorination hydrolysis reaction.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for preparing ferric hafniumate. Background Art

[0002] Ferric hafnium oxide is mainly added to ceramic matrix composites, which are the preferred materials for the hot end components of high thrust-to-weight ratio aircraft engines. Due to the high temperature, complex load and corrosive environment inside the engine, multilayer thermal barrier coatings are required to protect the high-temperature components of ceramic matrix composites. In multilayer thermal barrier coatings, the top coating is required to have good temperature bearing capacity, including high melting point, high temperature phase stability and sintering resistance; at the same time, it is also required to have matching mechanical and thermal properties to ensure strain tolerance and thermal insulation effect; in addition, as a coating directly facing the external environment, the top coating is required to be able to resist corrosion from low-melting oxides. Ferric hafnium oxide has a high melting point and excellent high temperature phase stability, and is one of the candidate materials for the top coating in multilayer thermal expansion coatings. Therefore, ferric hafnium oxide has a good application prospect in the field of corrosion-resistant and heat-resistant ceramics.

[0003] At present, the preparation method of hafnium oxide is: hafnium dioxide and ferric oxide are mixed evenly in a certain proportion, and then hafnium oxide ceramic powder is prepared by solid phase reaction method; then hafnium oxide ceramic powder is granulated by adding adhesive and appropriate mechanical treatment; then the granulated hafnium oxide powder is made into the required shape and size by isostatic pressing or other molding methods; finally, the formed hafnium oxide is sintered in a high temperature furnace to ensure the densification and grain growth of hafnium oxide. This method is a complete solid phase reaction, and the prepared hafnium oxide has an uneven texture and cannot meet the technical index requirements of high temperature resistant ceramic additives such as aircraft engine hot end components. Summary of the invention

[0004] In order to solve the technical problem that the iron hafnium oxide prepared by the current preparation method of iron hafnium oxide has uneven texture and cannot meet the technical index requirements of high-temperature ceramic additives for hot end components of aircraft engines, the present invention proposes a preparation method of iron hafnium oxide.

[0005] The technical solution of the present invention is:

[0006] A method for preparing ferric hafnium oxide, which is special in that it comprises the following steps:

[0007] Step 1, preparing iron hafnium fluoride;

[0008] Step 1.1: adding hafnium dioxide to hydrofluoric acid for heating and stirring reaction, and when the hafnium dioxide is dissolved to be colorless and transparent, a mixed solution of hafnium fluoroacid and hydrofluoric acid is obtained;

[0009] Step 1.2: adding ferric oxide to the mixed solution of hafnic acid and hydrofluoric acid, heating and evaporating to obtain a hafnic acid iron block; in this step, the liquid phase is mixed and evaporated to ensure that the materials are mixed evenly to the greatest extent;

[0010] Step 1.3: crushing and sieving the iron fluorohafnium oxide block to obtain iron fluorohafnium oxide powder; since iron fluorohafnium oxide is unstable, the iron fluorohafnium oxide powder is impure and part of the iron fluorohafnium oxide has been decomposed;

[0011] Step 2, preparing iron hafnium oxide;

[0012] Step 2.1: preparing the ferric fluorohalate powder into ferric fluorohalate sludge embryo with pure water / high purity water;

[0013] Step 2.2: heating the iron hafnium fluoride sludge to perform a defluorination hydrolysis reaction; since iron hafnium fluoride is unstable and easily hydrolyzed, it will hydrolyze and defluorinate to become oxides after adding water at high temperature, but it is not fixed and is in a powder state;

[0014] Step 2.3: Repeat steps 2.1-2.2, and when the fluoride ion is controlled to be less than 50 ppm, an amorphous hafnium oxide iron is obtained;

[0015] Step 2.4: The amorphous hafnium oxide is heated to a high temperature for high temperature shaping to obtain a finished hafnium oxide product in a porcelain-like form. The obtained hafnium oxide is tested, and the iron oxide content is 27-28%, and the hafnium oxide content is 72-73%.

[0016] Furthermore, the mass fraction of hydrofluoric acid in step 1.1 is 30-50%. If the mass fraction is too low, the reaction rate will be affected, and if the mass fraction is too high, it will be volatile and inconvenient to operate.

[0017] Furthermore, in step 1.1, the molar ratio of hydrofluoric acid to hafnium dioxide is 7-7.5:1.

[0018] Furthermore, in step 1.1, the temperature is raised to 80-100° C. and the reaction is carried out with stirring.

[0019] Furthermore, in step 1.2, the molar ratio of hafnium to iron is 1:1.

[0020] Furthermore, in step 1.2, the temperature is raised to 120-130° C. for evaporation to dryness.

[0021] Furthermore, in step 2.2, the fluorohafnium iron sludge is heated to 500-600°C for defluorination hydrolysis reaction for 5-8 hours; the temperature range here is the best range for taking into account both complete reaction and energy-saving production. If the temperature is lower than this range, the decomposition is incomplete, and if the temperature is higher than this range, it will cause waste of electricity.

[0022] Furthermore, in step 2.4, the amorphous hafnium oxide is heated to 1500-1700° C., and a high-temperature shaping treatment is performed for 2-3 hours at 1500-1700° C. (this temperature can sinter the hafnium oxide into a molten state to fix the crystal form, and if the temperature is higher than this range, it is difficult to reach on the equipment).

[0023] The reaction equation involved in the present invention is:

[0024] HkDJ 2 +6HF====H 2 FWf 6 +2H 2 O

[0025] 2H 2 FWf 6 +2HF+Fe 2 O 3 ====2FeHfF 7 +3H 2 O

[0026] 2FeHfF 7 +7H 2 O====Fe 2 Hf 2 O 7 +14HF

[0027] The advantages of the present invention are:

[0028] 1. The ferric hafnium oxide prepared by the present invention has uniform texture.

[0029] Since ferric hafnium oxide is a corrosion-resistant and high-temperature resistant ceramic additive, the most important requirement is that the texture needs to be uniform and no local unevenness can occur. If local unevenness occurs, local cracks may occur in a high-temperature environment, affecting the performance of the hot end components of the aircraft engine. In order to ensure the uniformity of the texture of the prepared ferric hafnium oxide, the present invention mainly takes the following measures: first, ferric oxide is added to a mixed solution of hafnic acid fluoroacid and hydrofluoric acid for liquid phase mixing and evaporation to ensure that the materials are mixed uniformly to the greatest extent; second, the ferric hafnium oxide powder is mixed with mud for multiple times and defluorinated hydrolysis reaction is carried out to ensure that the obtained ferric hafnium oxide has a uniform texture.

[0030] 2. The preparation method of the present invention is easy to operate and can be easily industrialized to produce ferric hafnium oxide. DETAILED DESCRIPTION

[0031] The present invention will be further described below by way of examples.

[0032] Example 1

[0033] In this example, iron hanate is prepared by the following steps

[0034] Step 1, preparation of ferric hafnium fluoride;

[0035] Step 1.1: add 50% hydrofluoric acid by mass into a tetrafluoroethylene beaker, add hafnium dioxide thereto, the molar ratio of hydrofluoric acid to hafnium dioxide being 7:1, heat to 90°C and stir to react, and when the hafnium dioxide is dissolved to be colorless and transparent, a mixed solution of hafnium fluoroacid and hydrofluoric acid is obtained;

[0036] Step 1.2: adding ferric oxide to the mixed solution of hafnium fluoroacid and hydrofluoric acid, wherein the molar ratio of hafnium to iron is 1:1, heating to 130° C. and evaporating to dryness to obtain a hafnium fluoroacid iron block;

[0037] Step 1.3: The ferric fluorohatenate block is crushed and passed through a 120-mesh sieve to obtain ferric fluorohatenate powder.

[0038] Step 2, preparing iron hafnium oxide;

[0039] Step 2.1: adding pure water to the ferric fluorohalate powder and mixing them, wherein the mass ratio of the ferric fluorohalate to the pure water is 3:1, to obtain a ferric fluorohalate sludge embryo;

[0040] Step 2.2: Place the iron fluorosulfate sludge in a platinum crucible and heat to 500° C. for defluorination hydrolysis for 6 hours;

[0041] Step 2.3: Repeat steps 2.1-2.2 for multiple times until the fluoride ion is controlled to be less than 50 ppm, thereby obtaining an amorphous hafnium oxide iron;

[0042] Step 2.4: Place the amorphous hafnium oxide iron in an alumina crucible, heat to 1700°C, and perform high temperature shaping for 2 hours to obtain a finished hafnium oxide iron product. The obtained finished hafnium oxide iron product was tested, and the iron oxide content was 27.2% and the hafnium oxide content was 72.6%, which met the customer's requirements.

[0043] Example 2

[0044] In this embodiment, iron hafnium oxide is prepared by the following steps:

[0045] Step 1, preparing iron hafnium fluoride;

[0046] Step 1.1: add 30% hydrofluoric acid by mass into a tetrafluoroethylene beaker, add hafnium dioxide thereto, the molar ratio of hydrofluoric acid to hafnium dioxide being 7.2:1, heat to 80°C and stir to react, and when the hafnium dioxide is dissolved to be colorless and transparent, a mixed solution of hafnium fluoroacid and hydrofluoric acid is obtained;

[0047] Step 1.2: adding ferric oxide to the mixed solution of hafnium fluoroacid and hydrofluoric acid, wherein the molar ratio of hafnium to iron is 1:1, heating to 125° C. and evaporating to dryness to obtain a hafnium fluoroacid iron block;

[0048] Step 1.3: The ferric fluorohatenate block is crushed and passed through a 125-mesh sieve to obtain ferric fluorohatenate powder.

[0049] Step 2, preparing iron hafnium oxide;

[0050] Step 2.1: adding pure water to the ferric fluorohalate powder and mixing them, wherein the mass ratio of the ferric fluorohalate to the pure water is 3.2:1, to obtain a ferric fluorohalate sludge embryo;

[0051] Step 2.2: placing the fluorohafnium iron sludge into a platinum crucible, heating to 550° C. and performing a defluorination hydrolysis reaction for 8 hours;

[0052] Step 2.3: Repeat steps 2.1-2.2 for multiple times until the fluoride ion is controlled to be less than 50 ppm, thereby obtaining an amorphous hafnium oxide iron;

[0053] Step 2.4: Place the amorphous hafnium oxide iron in an alumina crucible, heat to 1600°C, and perform high temperature shaping for 2.5 hours to obtain a finished hafnium oxide iron product. The obtained finished hafnium oxide iron product was tested, and the iron oxide content was 27.4% and the hafnium oxide content was 72.2%, which met the customer's requirements.

[0054] Example 3

[0055] In this embodiment, iron hafnium oxide is prepared by the following steps:

[0056] Step 1, preparing iron hafnium fluoride;

[0057] Step 1.1: add 40% hydrofluoric acid by mass into a tetrafluoroethylene beaker, add hafnium dioxide thereto, the molar ratio of hydrofluoric acid to hafnium dioxide being 7.5:1, heat to 100°C and stir to react, and when the hafnium dioxide is dissolved to be colorless and transparent, a mixed solution of hafnium fluoroacid and hydrofluoric acid is obtained;

[0058] Step 1.2: adding ferric oxide to the mixed solution of hafnium fluoroacid and hydrofluoric acid, wherein the molar ratio of hafnium to iron is 1:1, heating to 120° C. and evaporating to dryness to obtain a hafnium fluoroacid iron block;

[0059] Step 1.3: The ferric fluorohalate block is crushed and passed through a 130-mesh sieve to obtain ferric fluorohalate powder.

[0060] Step 2, preparing iron hafnium oxide;

[0061] Step 2.1: adding pure water to the ferric fluorohalate powder and mixing them, wherein the mass ratio of the ferric fluorohalate to the pure water is 3.5:1, to obtain a ferric fluorohalate sludge embryo;

[0062] Step 2.2: Place the iron fluorosulfate sludge in a platinum crucible and heat to 600° C. for defluorination hydrolysis reaction for 5 hours;

[0063] Step 2.3: Repeat steps 2.1-2.2 for multiple times until the fluoride ion is controlled to be less than 50 ppm, thereby obtaining an amorphous hafnium oxide iron;

[0064] Step 2.4: Place the amorphous hafnium oxide iron in an alumina crucible, heat to 1500°C, and perform high temperature shaping for 3 hours to obtain a finished hafnium oxide iron product. The obtained finished hafnium oxide iron product was tested, and the iron oxide content was 27.5% and the hafnium oxide content was 72.1%, which met the customer's requirements.

[0065] Example 4

[0066] In this embodiment, iron hafnium oxide is prepared by the following steps:

[0067] Step 1, preparing iron hafnium fluoride;

[0068] Step 1.1: add 45% hydrofluoric acid by mass into a tetrafluoroethylene beaker, add hafnium dioxide thereto, the molar ratio of hydrofluoric acid to hafnium dioxide being 7.3:1, heat to 100° C. and stir to react, and when the hafnium dioxide is dissolved to be colorless and transparent, a mixed solution of hafnium fluoroacid and hydrofluoric acid is obtained;

[0069] Step 1.2: adding ferric oxide to the mixed solution of hafnium fluoroacid and hydrofluoric acid, wherein the molar ratio of hafnium to iron is 1:1, heating to 130° C. and evaporating to dryness to obtain a hafnium fluoroacid iron block;

[0070] Step 1.3: The ferric fluorohatenate block is crushed and passed through a 115-mesh sieve to obtain ferric fluorohatenate powder.

[0071] Step 2, preparing iron hafnium oxide;

[0072] Step 2.1: adding pure water to the ferric fluorohalate powder and mixing them, wherein the mass ratio of the ferric fluorohalate to the pure water is 3.3:1, to obtain a ferric fluorohalate sludge embryo;

[0073] Step 2.2: placing the fluorohafnium iron sludge into a platinum crucible and heating the mixture to 520° C. for defluorination and hydrolysis for 5.5 hours;

[0074] Step 2.3: Repeat steps 2.1-2.2 for multiple times until the fluoride ion is controlled to be less than 50 ppm, thereby obtaining an amorphous hafnium oxide iron;

[0075] Step 2.4: Place the amorphous hafnium oxide iron in an alumina crucible, heat to 1650°C, and perform high temperature shaping for 3 hours to obtain a finished hafnium oxide iron product. The obtained finished hafnium oxide iron product was tested, and the iron oxide content was 27.4% and the hafnium oxide content was 72.3%, which met the customer's requirements.

Claims

1. A method for preparing ferric hafnium oxide, characterized in that: The following steps are involved: Step 1: Preparation of ferrous hafnium fluoride Step 1.1: adding hafnium dioxide to hydrofluoric acid for heating and stirring reaction, and when the hafnium dioxide is dissolved to be colorless and transparent, a mixed solution of hafnium fluoroacid and hydrofluoric acid is obtained; Step 1.2: adding ferric oxide to the mixed solution of hafnic acid and hydrofluoric acid, heating and evaporating to dryness, to obtain a hafnic acid iron block; Step 1.3: crushing and sieving the iron fluorohafnium oxide block to obtain iron fluorohafnium oxide powder; Step 2, preparing iron hafnium oxide; Step 2.1: preparing the ferric fluorohalate powder into ferric fluorohalate sludge embryo with pure water / high purity water; Step 2.2: heating the iron fluorohalate sludge embryo to carry out a defluorination hydrolysis reaction; Step 2.3: Repeat steps 2.1-2.2, and when the fluoride ion is controlled to be less than 50 ppm, an amorphous hafnium oxide iron is obtained; Step 2.4: heating the amorphous ferric hafnium oxide to perform high temperature shaping treatment to obtain a finished ferric hafnium oxide product.

2. The method for preparing ferric hafnium oxide according to claim 1, wherein: The mass fraction of hydrofluoric acid in step 1.1 is 30-50%.

3. The method for preparing ferric hafnium oxide according to claim 2, characterized in that: In step 1.1, the molar ratio of hydrofluoric acid to hafnium dioxide is 7-7.5:

1.

4. The method for preparing ferric hafnium oxide according to claim 3, characterized in that: In step 1.1, the temperature is raised to 80-100° C. and stirred to carry out the reaction.

5. The method for preparing ferric hafnium oxide according to claim 4, characterized in that: The molar ratio of hafnium to iron in step 1.2 is 1:

1.

6. The method for preparing ferric hafnium oxide according to claim 5, characterized in that: In step 1.2, the temperature is raised to 120-130° C. for evaporation to dryness.

7. The method for preparing ferric hafnium oxide according to claim 6, characterized in that: In step 2.2, the iron fluorosulfate sludge is heated to 500-600° C. for defluorination hydrolysis reaction for 5-8 hours.

8. The method for preparing ferric hafnium oxide according to claim 7, characterized in that: In step 2.4, the amorphous iron hafnium oxide is heated to 1500-1700° C. and subjected to high temperature shaping treatment for 2-3 hours.

9. A ferric hafnium oxide, characterized in that: The method is prepared by any one of claims 1 to 8.

10. A ceramic matrix composite material, characterized in that: The iron hafnium oxide according to claim 9 is used as an additive.